Traditional rainwater system to modern usage: a practical approach - Goh , Sin-Fui; Che-Ani, Adi-Irfan; Shaari, Nurulhuda; Mohd-Zain, Muhd-Fauzi; Surat, Mastor (2008)

(untitled)
Malaysia has a very high rainfall average through out the year. It is endowed with far more rainfall than the amount of water demand. Rainwater harvesting has been carried out for generations in many rural areas. Our rural communities have the traditional ways to collect rainwater. This paper describes our traditional harvesting system and how their system influences modern practice of rainwater harvesting. Thus our traditional harvesting is made compulsory as an essential knowledge when move forward to implement the modern rainwater harvesting. For a practical approach, rainwater harvesting system nowadays includes the catchments area, conveyance system, filtering, distribution system, and storage facility. Whereas, the traditional rainwater harvesting is simple, namely from the rooftop catchments and directly goes to cistern storage. But, with the advantage of city public water supply nowadays, people were forgotten about rainwater harvesting. Even in houses where gutter and down pipes are already fixed, rainwater is left to flow wastefully into the drainage system. Subsequent to the 1998 April drought, The Ministry of Housing and Local Government have expressed the Government’s interest for buildings to be designed to include rainwater harvesting system. The traditional practice of collecting rainwater where it falls has been revived to provide inexpensive water source for thousands of people. With the installation of rainwater harvesting system, it is yet to be hoped that in the near future; water users will not fully depending on public water supply.